Lazos parentales de adolescentes en etapa tardía de la ciudad de Bogotá - Gómez-Ramírez, Rocío Del Pilar (Infancias Imágenes, 2023)
This research paper studies the perception of parental ties in the late adolescent sub-stage. A sample of 281 young residents’ people has been participated in the city of Bogotá. For this, the Parental Bonding Instrument (PBI) was used in its version adapted for the Colombian population by Gómez, Vallejo, and Zambrano in 2007. This study pretend to provide information that allows intervention in areas of education and health related to family dynamics and paternal function. The results obtained presents a prevalence of perception of control-type bond without affection of 38,9% for each of the age range groups and statistically significant differences for sex, with a higher level of perception of paternal and maternal bond for the females. These data are like those found in previous research, both in prevalence and in differences according to established variables.